Empowerment of the Biology Subject Teacher Forum (MGMP) through Digital Innovation to Improve Scientific Literacy and Readiness for the Academic Ability Test (TKA) - Roza Helmita; m haviz; diyyan marneli; dwi kurnia fitri; Rina Delfita; Atiqa Zhafira Rinaldi; ervina ervina; aidhya Irhash Putra; najmiatul fajar; Ghinatul Mutmainah (MARAWA: Jurnal Masyarakat Religius dan Berwawasan, 2026)
This Community Service (PKM) activity aims to enhance the competence of Biology teachers in the Tanah Datar Regency Subject Teacher Forum (MGMP) in designing innovative digital instruction to support scientific literacy and students' readiness for the Academic Ability Test (TKA). The main problems of the partners were low technology utilization in teaching, limitations in developing assessments based on scientific literacy and Higher Order Thinking Skills, and the suboptimal role of the MGMP as a professional learning community. The activity employed the Asset-Based Community Development (ABCD) approach incorporating the stages of discovery, dream, design, define, and destiny integrated with hands-on training and collaborative mentoring. Held on December 17, 2025, at SMAN 1 Sungayang, the event involved 16 Biology teachers as participants. Results showed a significant improvement in teachers' understanding of scientific literacy and the TKA, evidenced by a rise in average scores from pre-test 62% to 85% on the post-test. Furthermore, there was an enhancement in digital pedagogical competence, with 90% of participants successfully integrating technology into instruction such as utilizing digital platforms, developing interactive media, and creating HOTS based assessments. The instructional products generated included digital learning kits, instructional videos, and TKA aligned test items, with 75% of these meeting high quality criteria. This program increased the participation of the teacher and strengthened the role of the MGMP as a sustainable professional learning community.